Regulation of globin-heme balance in Diamond-Blackfan anemia by HSP70/GATA1 - Rio, Sarah (Blood, 2019)
Diamond-Blackfan anemia (DBA) is a congenital erythroblastopenia that is characterized by a blockade in erythroid differentiation related to impaired ribosome biogenesis. DBA phenotype and genotype are highly heterogeneous. We have previously identified 2 in vitro erythroid cell growth phenotypes for primary CD34(+) cells from DBA patients and following short hairpin RNA knockdown of RPS19, RPL5, and RPL11 expression in normal human CD34(+) cells. The haploinsufficient RPS19 in vitro phenotype is less severe than that of 2 other ribosomal protein (RP) mutant genes. We further documented that proteasomal degradation of HSP70, the chaperone of GATA1, is a major contributor to the defect in erythroid proliferation, delayed erythroid differentiation, increased apoptosis, and decreased globin expression, which are all features of the RPL5 or RPL11 DBA phenotype. In the present study, we explored the hypothesis that an imbalance between globin and heme synthesis may be involved in pure red cell aplasia of DBA. We identified disequilibrium between the globin chain and the heme synthesis in erythroid cells of DBA patients. This imbalance led to accumulation of excess free heme and increased reactive oxygen species production that was more pronounced in cells of the RPL5 or RPL11 phenotype. Strikingly, rescue experiments with wild-type HSP70 restored GATA1 expression levels, increased globin synthesis thereby reducing free heme excess and resulting in decreased apoptosis of DBA erythroid cells. These results demonstrate the involvement of heme in DBA pathophysiology and a major role of HSP70 in the control of balanced heme/globin synthesis.